The Influence of Employer Branding and Career Development on the Interest of Job Candidates in Startup Companies - Khairunnisah, Noni Antika; Gunardi, Effendy; Karmeli, Elly; Halik, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research aims to analyze the influence of employer branding and career development on the interest of job applicants in startup companies. The background of this research is based on the increasing competition for startup companies in recruiting the best talent amidst limited resources and an unestablished company image. The research method used is associative quantitative with a survey approach. Data was obtained from 120 respondents who were job seekers aged 20–35 years who were interested in working in startup companies. The sampling technique used purposive sampling and data analysis was carried out using multiple linear regression. The research results show that employer branding has a positive and significant effect on the interest of job applicants. Likewise, career development also has a positive and significant effect on the interest of job applicants. Simultaneously, these two variables have a significant effect on job applicant interest, with a coefficient of determination value of 48.6%. These findings indicate that startup companies need to develop a strong branding strategy and a structured career development system to increase their attractiveness in the eyes of potential applicants.